Identification of Protein Functional Regions. Issue 4 (16th January 2020) - Nerattini, Francesca; Figliuzzi, Matteo; Cardelli, Chiara; Tubiana, Luca; Bianco, Valentino; Dellago, Christoph; Coluzza, Ivan
Abstract: Protein sequence stores the information relative to both functionality and stability, thus making it difficult to disentangle the two contributions. However, the identification of critical residues for function and stability has important implications for the mapping of the proteome interactions, as well as for many pharmaceutical applications, e. g. the identification of ligand binding regions for targeted pharmaceutical protein design. In this work, we propose a computational method to identify critical residues for protein functionality and stability and to further categorise them in strictly functional, structural and intermediate. We evaluate single site conservation and use Direct Coupling Analysis (DCA) to identify co‐evolved residues both in natural and artificial evolution processes. We reproduce artificial evolution using protein design and base our approach on the hypothesis that artificial evolution in the absence of any functional constraint would exclusively lead to site conservation and co‐evolution events of the structural type. Conversely, natural evolution intrinsically embeds both functional and structural information. By comparing the lists of conserved and co‐evolved residues, outcomes of the analysis on natural and artificial evolution, we identify the functional residues without the need of any a priori knowledge of the biological role of the analysed protein. Abstract : Natural sequences contain residues essential for the protein function and its structural stability. Conversely, artificially designed folding protein sequences have only structural residues. With our novel comparative analysis of natural and artificial folding sequences, we can successfully annotate residues.